Pengaruh Promosi Melalui Media Sosial Instagram dan Online Customer Review di Aplikasi Pesan Antar Makanan Terhadap Minat Beli Konsumen UMKM Eloka Corndog Kota Jambi - Chinta Yurike Utomo; Efni Anita; Nurrahma Sari Putri (UNIVERSITAS MARITIM AMNI SEMARANG, 2024)
This research aims to determine and analyze the influence of the independent variable on the dependent variable. The method used in this research is a quantitative method. The sample in this study was 100 active Instagram users around the MSME Eloka Corndog, Jambi City. The research results show that social media (X1) has a significant effect on consumer buying interest (Y) with a Tcount value of 3.176>Ttable 1.984 and a Sig value of 0.002<0.05, which means Ho is rejected and Ha is accepted. Online Customer Review (X2) shows that there is a significant influence on Consumer Purchase Interest (Y). with a calculated T value for the Online Customer Review variable of 7,736>1.984 with a significance value of 0.001<0.05. So it can be concluded that Ho is rejected and Ha is accepted. Simultaneously (X1), (X2) and (X3) simultaneously influence (Y) by 0.000<0.005 and the value of Fcount > Ftable 163,368>3.10.